Sosialisasi tentang Bahaya Bahan Kimia Obat di dalam Jamu dan Kosmetik Palsu - Indrasari, Ferika; Cristiani, Odilia Dhea; Novembrina, Metrikana; Indrianawati, Rita; Herdias, Herdias (Universitas Pahlawan Tuanku Tambusai, 2025)
Herbal remedies are among the traditional medicine products that are highly favored by the Indonesian population. Herbal remedies should not include chemical drug components as they pose health risks. The impact of using herbal medicine along with extra BKO can range from minor ailments to serious life-threatening issues. Besides herbal medicine, numerous counterfeit cosmetic items have also been found to include harmful substances. This is derived from the findings of BPOM testing on herbal medicine and cosmetic samples available in the market. The activity seeks to educate on the risks associated with chemical drugs used in herbal medicine and the hazards posed by counterfeit cosmetics. The approach to assess both initial and final knowledge involves completing a questionnaire, while counseling occurs through lectures, discussions, and QA sessions. The outcomes of the counseling activities that were conducted proceeded as intended and were effective. The evaluation results from before (pretest) and after the counseling (post-test) indicate that the significance value is 0.000 (0.05). This indicates that participants enhanced their understanding following the counseling sessions conducted.